Dyckia magnifica, a new species of Bromeliaceae (Pitcairnioideae) from Southern Brazil, and the re-establishment of D. tomentosa, of the D. selloa complex - Büneker, Henrique Mallmann; Pastori, Tamara; Schwambach De Almeida, Pedro; de Araujo Mariath, Jorge Ernesto (Phytotaxa, 2023)
We propose the re-establishment of Dyckia tomentosa, after rediscovering its populations, the synonymization of Dyckia polyclada, and Dyckia magnifica as a new species from southern Brazil that is morphologically related to D. tomentosa. Descriptions of external morphology, leaf anatomy and pollen morphology, and comments on species distributions and habitats are provided. The informal species complex in which D. magnifica and D. tomentosa are placed is morphologically re-circumscribed and proposed here as the “Dyckia selloa complex”.